Extending the range of Plasmodium falciparum transmission blocking antibodies. Issue 21 (16th May 2023) - Simons, Lacy M.; Ferrer, Patricia; Gombakomba, Nita; Underwood, Knashka; Herrera, Raul; Narum, David L.; Canepa, Gaspar; Acquah, Festus; Amoah, Linda; Duffy, Patrick E.; Barillas-Mury, Carolina; Long, Carole; et al.
Abstract: Recent work demonstrating that asymptomatic carriers of P. falciparum parasites make up a large part of the infectious reservoir highlights the need for an effective malaria vaccine. Given the historical challenges of vaccine development, multiple parasite stages have been targeted, including the sexual stages required for transmission. Using flow cytometry to efficiently screen for P. falciparum gamete/zygote surface reactivity, we identified 82 antibodies that bound live P. falciparum gametes/zygotes. Ten antibodies had significant transmission-reducing activity (TRA) in a standard membrane feeding assay and were subcloned along with 9 nonTRA antibodies as comparators. After subcloning, only eight of the monoclonals obtained have significant TRA. These eight TRA mAbs do not recognize epitopes present in any of the current recombinant transmission-blocking vaccine candidates, Pfs230D1M, Pfs48/45.6C, Pf47 D2 and rPfs25. One TRA mAb immunoprecipitates two surface antigens, Pfs47 and Pfs230, that are expressed by both gametocytes and gametes/zygotes. These two proteins have not previously been reported to associate and the recognition of both by a single TRA mAb suggests the Pfs47/Pfs230 complex is a new vaccine target. In total, Pfs230 was the dominant target antigen, with five of the eight TRA mAbs and 8 of 11 nonTRA gamete/zygote surface reactive mAbs interacting with Pfs230. Of the three remaining TRA mAbs, two recognized non-reduced, parasite-produced Pfs25 and one bound non-reduced, parasite-produced Pfs48/45. None of the TRA mAbs bound protein on an immunoblot of reduced gamete/zygote extract and two TRA mAbs were immunoblot negative, indicating none of the new TRA epitopes are linear. The identification of eight new TRA mAbs that bind epitopes not included in any of the constructs currently under advancement as transmission-blocking vaccine candidates may provide new targets worthy of further study.